Cost–utility analysis of individual psychosocial support interventions for breast cancer patients in a randomized controlled study. Issue 3 (23rd September 2013) - Arving, Cecilia; Brandberg, Yvonne; Feldman, Inna; Johansson, Birgitta; Glimelius, Bengt
Abstract Objectives The aim was to explore the cost–utility in providing complementary individual psychosocial support to breast cancer patients compared with standard care (SC). Methods Patients just starting adjuvant therapy (n = 168) at Uppsala University Hospital, Sweden, were consecutively included and randomized into three groups: psychosocial support from a specially trained nurse (INS), from a psychologist (IPS), or SC. Psychological effects and healthcare utilization were monitored during a 2‐year period. The hospital billing system provided cost estimates. Quality‐adjusted life years (QALYs) were calculated using health‐related quality of life data from the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ C‐30) translated into the Euro Quality of Life‐ 5‐Dimensional classification. On the basis of the medical cost offset, a cost–utility analysis was performed. Results Health care utilization was mainly related to the breast cancer diagnosis and treatment. The intervention costs amounted to about €500 or 3% of the total costs. Total health care costs, including interventions cost, were lower in the INS (€18, 670) and IPS (€20, 419) groups than in the SC group (€25, 800). The number of QALYs were also higher in the INS (1.52 QALY) and IPS (1.59 QALY) groups, compared with the SC group (1.43 QALY). Conclusions The cost–utility analysis revealed that, during adjuvant treatment for breast cancer, the individual psychosocial support interventions provided here was cost effective because the health care costs were lower and QALYs were higher compared to SC alone. Copyright © 2013 John Wiley & Sons, Ltd.